Commissions of inquiry in Sri Lanka: A critical analysis of the dual statutory framework and its role in democratic governance - Harankaha, M.; Thilakarathna, K.A.A.N.; Weerasinghe, M.G.H.P. (University of Colombo, 2025)
This research paper provides a critical examination of Sri Lanka’s two-fold statutory framework relating to commissions of inquiry, the Commissions of Inquiry Act No. 17 of 1948 and the Special Presidential Commissions of Inquiry Law No. 7 of 1978. Under these two instruments, Sri Lanka has seen the creation of a number of ad hoc investigative bodies under President’s warrant, to inquire into matters of national significance and controversy, including high-end corruption, maladministration, political victimization, and systematic abuses of power involving public figures and public officers. Employing a qualitative methodology based on doctrinal analysis and supported by case-based research, this study explores the legal foundations and coercive powers of both types of commissions, examining how these elements shape their role in Sri Lanka’s governance framework. Despite both frameworks bearing resemblances with each other, a comparative analysis of corresponding provisions of both legislations mentioned above reveals that they differ fundamentally in their structure, powers and effect. While the commissions under 1948 Act function primarily as non-binding fact-finding bodies with procedural flexibility and broader public engagement, the commissions under 1978 Law exercise quasi-judicial power, with more coercive investigative authority, and the power to impose civic disabilities, coupled with ouster clauses preventing judicial review of the commissions’ findings. The paper explores the inherent structural deficiencies and procedural limitations that undermine the effectiveness of these mechanisms, with a special focus on the judiciary’s attitude towards scrutinizing the Special Presidential Commissions of Inquiry. Overall, this study attempts to highlight the important role of these institutions as a means of a complementary mechanism which promotes the democratic governance, and transparency; crucial in restoring public trust and effectuating justice in Sri Lanka’s transitional economic, political and constitutional landscape.
Keywords: Commissions of inquiry; Accountability mechanisms; Quasi-Judicial powers; Democratic governance